Observational techniques to assist the coupling of CWE/CFD models and meso-scale meteorological models. Issue 144 (September 2015) - Emeis, Stefan
Abstract: Coupling micro-scale computational wind engineering (CWE) and computational fluid dynamics (CFD) models with meso-scale meteorological models (MMMs) is known to be hampered by the problem of adequately representing turbulence and thermal convection in these models either through a parameterization or by fully resolving them. There is a third class of motions which adds to this problem: surface-induced secondary circulations (SISCs). SISCs have similar spatial scales as thermal convection. Furthermore, low-level jets are identified as an additional regional-scale wind phenomenon which needs attention in coupling micro-scale and meso-scale models. This review paper discusses this issue from the viewpoint of providing meteorological data for model validation. Surface-based remote sensing is suggested for the purpose of exploring these wind phenomena between the micro-scale and meso-scale. This measurement technique is able to deliver the necessary data to evaluate the approaches towards a successful coupling of micro-scale and meso-scale models.